Implementation Of Excellent Service By Front Office Department To Increase Guest Satisfaction At Kayumanis Jimbaran Private Estate And Spa - Paramitha P, Putu Ayu Sari Pradnya; Winia, I Nyoman; Armoni, Ni Luh Eka (Politeknik Sahid, 2022)
Purpose: This study focuses on implementing excellent service based on or guided by standard operating procedures by looking at the operational conditions that took place in a specified period. The purpose of this study was to determine the application of excellent service by the front office department to increase satisfaction and assess the level of guest satisfaction with service by implementing excellent service to find out how effectively excellent service is applied in standard operating procedures to create unique and quality services.Methods: This study uses a qualitative descriptive method by comparing the percentage value to determine the difference of each indicator in the applicable standard operating procedure so that data can be presented to conclude. Data collection methods in this study are observation, interviews, documentation, literature study, and data reduction using a questionnaire.Results and discussion: The results of this study indicate that all front office department employees at Kayumanis Jimbaran Private Estate And Spa have implemented excellent service in all existing operations by standard operating procedures. Traditional operating systems are designed to facilitate front-office department employees in daily operational processes and as a basis for providing services.Implication: The implementation of excellent service by the front office department at Kayumanis Jimbaran Private Estate And Spa has been effectively implemented and provides satisfaction according to customer expectations.